Temperature-responsive PLLA/PNIPAM nanofibers for switchable release - Elashnikov, Roman; Slepička, Petr; Rimpelova, Silvie; Ulbrich, Pavel; Švorčík, Vaclav; Lyutakov, Oleksiy (Materials science & engineering. C, Materials for biological applications, 2017)
Smart antimicrobial materials with on-demand drug release are highly desired for biomedical applications. Herein, we report about temperature-responsive poly(N-isopropylacrylamide) (PNIPAM) nanospheres doped with crystal violet (CV) and incorporated into the poly-l-lactide (PLLA) nanofibers. The nanofibers were prepared by electrospinning, using different initial polymers ratios. The morphology of the nanofibers and polymers distribution in the nanofibers were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The interaction between PNIPAM and PLLA in the nanofibers was studied by Fourier transform infrared spectroscopy (FTIR) and its effect on the PNIPAM phase transition was also investigated. It was shown that by the changing of the environmental temperature across the lower critical solution temperature (LCST) of PNIPAM, the switchable wettability and controlled CV release can be achieved. The temperature-dependent release kinetics of CV from polymer nanofibers was investigated by ultraviolet-visible spectroscopy (UV-Vis). The temperature-responsive release of antibacterial CV was also tested for triggering of antibacterial activity, which was examined on Staphylococcus epidermidis (S. epidermidis) and Escherichia coli (E. coli). Thus, the proposed material is promising value for controllable drug-release.
Keywords: Acrylic Resins; mikroskopie elektronová rastrovací; nosiče léků; teplota; Wettability; Electrospinning; Stimuli-responsive; antiinfekční látky lokální; Gentian Violet; uvolňování léčiv; akrylové pryskyřice; Polyesters; Temperature; Drug Liberation; Polymer blends; polyestery; Antibacterial; Microscopy, Electron, Scanning; Responsive release; smáčivost; mikroskopie atomárních sil; Switchable wettability; spektroskopie infračervená s Fourierovou transformací; Staphylococcus epidermidis; Microscopy, Atomic Force; Nanofibers; genciánová violeť; Spectroscopy, Fourier Transform Infrared; Anti-Infective Agents, Local; nanovlákna; změna skupenství; Phase Transition; Drug Carriers; Escherichia coli